The history book (Big ideas simply explained, 2016)
Travel back in time with the latest instalment in the bestselling Big Ideas series.The History Book charts world history from the dawn of civilisation to the modern culture we live in today. From the origins of homo-sapiens to the release of Nelson Mandela, from the French Revolution to the Space Race, The History Book is a stunning exploration of the human timeline up to and including modern Islam, the world wide web, and the global financial crisis.The History Book tackles big historical ideas with stunning visuals, key quotes, and important themes that are woven throughout world history. Discover events from the assassination of Caesar to World War I and see the people and events come to life with The History Book, perfect for students, adults, or anyone who wants to understand our fascinating past.